Chaperone-assisted soluble expression and characterization of chitinase chiZJ408 in Escherichia coli BL21 and the chitin degradation by recombinant enzyme. Issue 3 (1st March 2022) - Yu, Ping; Wang, Xinxin; Ma, Jian; Zhang, Qili; Chen, Qingwei
Abstract: The chaperone-assisted soluble expression and characterization of high molecular weight chitinase chiZJ408 in Escherichia coli BL21 were investigated. Chitin degradation products by chitinase chiZJ408 were analyzed. The results indicated that the introduction of the chaperone GroELS promoted the correct folding of chitinase chiZJ408 and increased its soluble expression by 14.9% ( p < 0.05) in E. coli BL21. The optimal pH and temperature of chitinase chiZJ408 were respectively 6.0 and 50 °C. Chitinase chiZJ408 was stable at pHs of 4.0 ∼ 7.0 and at below 40 °C. Mg 2+ and Ca 2+ had a significant impact on improving the activity of chitinase chiZJ408. Chitinase chiZJ408 was demonstrated to be exochitinase that cleaved the β -1, 4-glycosidic bond of the chitin chain to generate only N, N' -diacetylchitobiose. This study broadens our understanding of chitinase and provides a basis for solving the problem of inclusion body formed by long fragment gene expression in E. coli .